PENGARUH KEPEMIMPINAN, KECERDASAN EMOSIONAL DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA GURU DI SMA - AHMAD FAUZI (Universitas Negeri Jakarta, 2011)
The purpose of this study was to obtain information about the influence of leadership, emotional intelligence and work motivation on teacher’s job satisfaction. This research was conducted by survey on state senior high school of West Java, with sample of 100 permanent teachers of proportional random sampling technique. Analyzing of the data, study was conducted with using MINITAB statistical 14 and SPSS 17 program.The study found that there is direct and significant influence of the leadership of school principal on work motivation; There is direct and significant influence of EQ on work motivation; There is direct and significant influence of the leadership of school principal on job satisfaction; There is indirect significant influence of EQ on job satisfaction through work motivation; There is direct and significant influence of work m otiation on job satisfaction.